PENGARUH FAMILY OWNERSHIP DAN INSTITUTIONAL OWNERSHIP TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur Indonesia) - Faizal Endi Wibowo; Erman Denny Arfianto (Faculty of Economics and Business Diponegoro University, 2022)
This Study aims to prove the effect of Family Ownership and Institutional Ownership, on the dividend payout ratio in Indonesia. According to a recent study (Mulyani, Singh, & Mishra, 2016) shows that family ownership has a negative effect on dividend payout. But in the other recent study (Setianto & Sari, 2017) says that family ownership has a positive effect on dividend payout. These are the cause of why we strive to seek the truth about the relationship between family ownership and dividend payout in Indonesia. This study's initial sample includes all the listed manufacture company in Indonesian Stock Exchange from 2013 to 2021. This study will not include firms that did not pay dividends during the 2013-2021 periods. All those sorted samples will be sorted again into family-owned firms that meet the category. Our data were collected from the Indonesian Stock Exchange's official website and from Bloomberg. The ownership data was collected manually. This study will use ordinary least square regression. This study provides proof that family ownership has no effect on the dividend payout. And in this study, we prove that Institutional Ownership has a negative and significant effect on Dividend Payout Ratio.